(untitled) (American Journal of Technology and Applied Sciences, 2023)
Mixed-ligand coordination compounds of calcium acetate have been synthesized. The composition, identity, methods of coordination of acetate groups, molecules of formamide, acetamide, carbamide, thiocarbamide have been established, and the thermal behavior of the obtained complexes has been studied.